Desdobramentos contemporâneos: processos híbridos entre Origami, Op Art e tecnologia - Massoli, Emerson da Silva (2022)
The present research in visual poetics, linked to the Art and Technology line, of the Graduate Program in Visual Arts, proposes the establishment of artistic installations, from physical and digital elements, resulting from the Origami technique and images referenced in the Movement artistic Op Art, through the investigation of hybrid processes in Contemporary Art. The poetics is based on the practical and theoretical conceptualization of the hybrid process between Crafts and technologies, in-depth, from the author's own artistic practice. Thus, the term Craft refers to predominantly manual techniques, in which the artist explores his subjectivity through direct physical contact with materials and tools. In the context of the research, the manuality is in the paper folding technique, the Origami; in turn, the technologies used are related to the construction of images inspired by Op Art, in this case, digital technologies, involved in devices and software, employed in the poetics in a semi-automated way. The study is developed motivated by the contemporary phenomena of instability, ephemerality and transience, resulting from the condition of life in Post-Modernity, affecting all dimensions of the subjects inserted in this context. Such circumstances, observed in the author's personal life, serve as a stimulus for the initiation of the works. Conceptions are developed, through analogies between the hybrid processes, the Origami technique and the historical and aesthetic aspects of Op Art with PostModernity, aiming to establish a link between the topics covered, in the perspective of interrelating in a subjective and personal, the artistic practice with the theory involved in the research. In addition, topics related to appropriation and visual perception associated with Art are addressed. Through poetics, the possible developments in Contemporary Art are investigated and analyzed, through the hybridism between Art and Technology, resulting in eight artistic proposals, covering the study topics, which are presented to the public in three individual exhibitions, permeating the hybridism between materiality and virtuality in interactive propositions.